Metamorphic evolution of ultrahigh-pressure garnet peridotites from the Variscan Vosges Mts. (France) - Altherr, Rainer; Kalt, Angelika (Chemical geology, 1996)
In the Central Vosges Mts. (France) of the Variscan belt, MgCr garnet peridotite bodies occur within the uppermost tectonometamorphic unit (Leptynitic granulites) as lenses in low-pressure/high-temperature metamorphic rocks. Neglecting late-stage serpentinization, the metamorphic evolution of these rocks was characterized by four stages. During stage I, the rocks were equilibrated at high pressures and temperatures (> 4.9 GPa/ > 950°C, in most cases > 1100°C), either within or near to the stability field of diamond. Stage II is documented by the formation of coronas around relict garnet with the assemblage orthopyroxene ± clinopyroxene ± amphibole + spinel ± plagioclase. During stage III, the remaining garnet was transformed to very fine-grained kelyphite consisting of orthopyroxene + amphibole + spinel ± plagioclase. Small relict garnet grains are preserved in one peridotite only. Stage IV corresponds to the late formation of tremolitic hornblende and chlorite which partially replaced the pseudomorphs after garnet or occur along cracks in the matrix of some rocks. Compositional zoning patterns of pyroxene porphyroclasts suggest that initial decompression was either accompanied by a moderate increase in temperature or nearly isothermal. Garnet breakdown textures and compositions of minerals grown during stages II and III also suggest rapid decompression at still elevated temperatures (1000-720°C).
Elektronische Reproduktion der Druck-Ausgabe 22. Februar 1999
Gesehen am 05.12.2022